SAĞLIKTA DÖNÜŞÜM PROGRAMI SONRASI SAĞLIK HIZMETI MEMNUNIYETI: İSTANBUL ÖRNEĞI - YILMAZ, GÜLAY (My University, 2019)
Türkiye’de daha etkin sağlık hizmeti sunumu hedefine yönelik olarak 2003 yılı itibarıyla Sağlıkta DönüşümProgramı uygulamaya geçirilmiştir. Bu uygulama ile sağlık hizmetinin sunumunda ve finansmanında reformgerçekleştirilmiştir. Söz konusu reformlar ile bir taraftan halkın sağlık hizmetine erişimini kolaylaştırmakdiğer taraftan da maliyet etkinliği sağlanmaya çalışılmıştır. Bu bağlamda bir dizi tedbir uygulamayakonulmuştur. Hizmet sunumu alanındaki reformun en önemli yapı taşları; ilk adım sağlık hizmetininkırsalda sağlık evi ve ocakları, kentlerde aile hekimleri tarafından vatandaş odaklı olarak sunumuna geçiş,hastanelerde randevu sistemine geçiş ve özel hastanelerden faydalanabilme imkanlarının genişletilmesiolmuştur. Hizmetin finansmanında reformun temel taşlarını ise; sağlık sigorta sisteminin tek çatı altındatoplanması, 2006 yılından itibaren performans sisteminin uygulamaya geçirilmesi ve ilaç sektörünüdüzenleyici tedbirler oluşturmuştur. Ölçülebilir performans uygulamaları ile aynı miktar faktör ile (sağlıkçalışanı) bir taraftan mümkün olduğunca daha fazla kişiye hizmet üretimi, diğer taraftan bunun ücreteyansıması hedeflenmiştir. İlaç sektörünü düzenleyici uygulamalar ile tedavi edici sağlık hizmetleri maliyetiniazaltmak, genel sağlık sigortasına geçiş ile sağlık hizmetini üretmeye yönelik daha etkin bir kaynak yönetimisağlanmaya çalışılmıştır. Bahsedilen uygulamalar hizmeti talep eden hastalar üzerinde etkili olmuştur.Çalışmamızda, İstanbul’da yaşayan bireylerin sağlık hizmeti memnuniyeti ölçülmeye çalışılmıştır.

Health Transformation Programme was started to apply since 2003, directed to reach the aim of more efficient health service in Turkey. With this programme, a reform was tried to be realized at the health service supply at the same time with a reform at the finance of health services. With the reforms that mentioned above, the cost efficiency was tried to be ensured as well as making easy the access to the health services. In that context, a series of measures applied. The most important milestones of the reform at the service supply area as follows; the transition of the health services to the citizen focused supply by the health houses and community health centers at the rural areas, and by the primary health services at the urban areas. The transition to the appointment system at hospitals and the extend of opportunities on the utilization from the private hospitals. The main pillars of the reform at the finance of the services are as follows; convergence of the health insurance system, applying the performance measurement system since 2006 and the regulative measures for the pharmaceutical industry. With the measurable performance applications, the service production for the most possible quantity of people with the same quantity of factors (health sector employees); at the same time, reflections of that on the prices were aimed. With the regulative applications at the pharmaceutical sector, lowering the cost of health services was aimed, with the transition to the general health insurance system, more efficient source management that is directed produce health service production was tried to be ensured. The applications that mentioned above have been influential on the patients who demand the health services. In our research project, we tried to measure the satisfaction level of patients who live in Istanbul, regarding the health service.
HEALTH SERVICES SATISFACTION SURVEY AFTER THE HEALTH TRANSFORMATION PROGRAMME: ISTANBUL CASE
Keywords: Sağlık Bilimleri ve Hizmetleri; Tıbbi İnformatik; Temel Sağlık Hizmetleri; Sağlık Politikaları ve Hizmetleri